Generation of Massively Entangled Bright States of Light during Harmonic Generation in Resonant Media - Sili Yi; Nikolai D. Klimkin; Graham Gardiner Brown; Olga Smirnova; Serguei Patchkovskii; Ihar Babushkin; Misha Ivanov (Physical Review X)
At the fundamental level, full description of light-matter interaction requires quantum treatment of both matter and light. However, for standard light sources generating intense laser pulses carrying quadrillions of photons in a coherent state, the classical description of light during intense laser-matter interaction has been expected to be adequate. Here, we show how nonlinear optical response of matter can be controlled to generate dramatic deviations from this standard picture, including generation of several squeezed and entangled harmonics of the incident laser light. In particular, such nontrivial quantum states of harmonics are generated as soon as one of the harmonics induces a transition between different laser-dressed states of the material system. Such transitions generate an entangled light-matter wave function, which can generate quantum states of harmonics even in the absence of a quantum driving field or material correlations. In turn, entanglement of the material system with a single harmonic generates and controls entanglement between different harmonics. Hence, nonlinear media that are near resonant with at least one of the harmonics appear to be quite attractive for controlled generation of massively entangled quantum states of light. Our analysis opens remarkable opportunities at the interface of attosecond physics and quantum optics, with implications for quantum information science.